The Effectiveness of Public Relations Communication in the Public Service Acceleration Programme related to Digitalisation at Bank Sumut - Aprilla Rasyidin Batubara (Yayasan Al'Adzkiya Rantauprapat, 2025)
This study was motivated by the phenomenon of risks affecting the use of Sumut Mobile Banking, such as debited transactions occurring due to human error or application system malfunctions, and the possibility of account hacking due to viruses (malware) entering mobile phones and attacking various applications, one of which may be the Sumut Mobile application. This has become one of the reasons customers consider using Sumut Mobile. The research method used was descriptive with qualitative analysis. The research data was obtained through interviews with four sources who were employees of Bank Sumut. Based on the results of the study, the role of public relations has proven to be very effective in improving the public service acceleration programme related to digitalisation at Bank Sumut. The public relations team plays an important role in designing and implementing communication strategies that successfully promote the bank's digitalisation initiatives to the public. Through creative marketing campaigns and transparent communication, public relations has succeeded in increasing public awareness and acceptance of the digital services offered by Bank Sumut. Thus, the role of public relations has proven to be one of the main pillars in the success of the public service acceleration programme related to digitalisation at Bank Sumut.